(untitled) (Indonesian Art and Justice Review, 2025)
In Indonesia, mental health remains a stigmatized and often overlooked issue, particularly in marginalized communities. This paper explores the therapeutic role of art in addressing mental health challenges and promoting social justice. Focusing on art therapy practices, community art projects, and grassroots movements, the study highlights how creative expression is being used as a tool for mental healing, self-expression, and social inclusion. By examining case studies from various regions, the paper explores how art provides a safe space for individuals affected by trauma, depression, and anxiety, while also empowering them to share their personal stories and advocate for greater mental health support and awareness. The study also considers how art-based interventions are helping to break down stigma and foster a more inclusive approach to mental health care in Indonesia.